81 Meeting in the metaverse - a new paradigm for scientific mentorship. (6th June 2022) - Radford, Danny; Ahmed, Samahat; Tai Loy Lee, Teddy; Hui, Jeremy Man Ho; Lee, Yan Hiu Athena; Iltaf Satti, Danish; Roever, Leonardo; Liu, Tong; Ciobanu, Ana; Mahmoudi, Elham; Chan, Jeffrey Shi Kai; Tse, Gary
Abstract : Introduction: The metaverse, first conceptualised in science fiction, has gradually become a reality and incorporated into our daily lives. Recent work has focused on the delivery of teaching using such platforms. In this study, we share our initial experience of the Cardiovascular Analytics Group, an online mentorship platform with recent innovations in incorporating our mentorship activities in the metaverse. Methods: This was a two-part prospective study conducted over four weeks. All participants provided informed consent for the use of their avatars as well as oral and written responses for publication. Invitations were sent to all group members along with joining instructions for AltspaceVR, a metaverse platform. Meet and greet and informal drop-in sessions were held weekly for four weeks. Hybrid sessions were provided involving both the metaverse platform and with direct streaming to Microsoft Teams for the Group's monthly meeting. Surveys were sent to solicit their views and experiences on the metaverse. Questions focused on its roles in facilitating virtual mentorship including accessibility, communication and internationalisation. Results: Our group currently consists of 86 members from 20 countries. Of these, 23 members participated in the metaverse. A total of 18 members (78%) responded to our survey (mean age: 28±7 years old; 28% female). On a scale of 1 to 5 (from least to most satisfied), 78% of members were satisfied with the platform. After the series of sessions, 72% of members found that the platform facilitated interactions with new members and 67% found the platform facilitated interactions with members from other countries more than traditional video platforms alone. Additionally, 18/18 members (100%) indicated that the metaverse platform was equally or more effective for project-related tasks compared to traditional communication methods such as emails. Notably, 15/18 members (83%) indicated that they enjoyed the gamification aspect of the metaverse, 7/18 members (39%) stated this prompted their interests for participating in medical research and 13/18 members (73%) agreed this facilitated mentorship. Conclusion: The metaverse is an effective system for facilitating and enabling interactions amongst international colleagues, breaking down barriers between colleagues from different countries and across traditional hierarchies. Conflict of Interest: N/A